Cultures in Contact : World Migrations in the Second Millennium - Hoerder, Dirk (Book collections on Project MUSE., 2002)
[This book] provides a history of the world told through the movements of its people. It is a broad ... interpretation of the scope, patterns, and consequences of human migrations over the past ten centuries. In this [book, the author] reconceptualizes the history of migration and immigration, establishing that societal transformation cannot be understood without taking into account the impact of migrations and ... that mobility is more characteristic of human behavior than is stasis. [This book] creates an English-language map of human movement that is not Atlantic Ocean based. [The author] describes the origins, causes, and extent of migrations around the globe and analyzes the cultural interactions they have triggered. He pays particular attention to the consequences of immigration within the receiving countries. His work sweeps from the eleventh century forward through the end of the twentieth ...-Dust jacket.